Design of a resilient ring for middle ear's chamber stapes prosthesis. Issue 15 (18th November 2018) - Kiryk, Emilia Anna; Kamieniecki, Konrad; Kwacz, Monika
Abstract: This paper presents the process of designing a new elastic element replacing a membrane in the chamber stapes prosthesis (ChSP). The results of the study are volume displacement characteristics obtained for the prosthesis and physiological stapes. Simulation tests on a 3D CAD model have confirmed that a properly designed ring can stimulate perilymph with the same or greater efficacy as the physiological stapes footplate placed on the elastic annular ligament. The ChSP with a new elastic element creates a good chance of improving hearing in patients suffering from otosclerosis.